2001
DOI: 10.1113/eph8602114
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Basis of Uterine Contractility: A Short Review

Abstract: In this review we discuss our current understanding of the cellular basis of uterine contractility, highlighting those areas requiring further study. It is clear that the basic processes of excitation‐contraction coupling lie within the myometrial cell, and that these may be modified by agonists. Pacemaker acitivity, however, remains a mystery. The contribution of extracellular calcium entry to contraction is shown to be vital, whilst the role of the sarcoplasmic reticulum remains controversial. Much current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 55 publications
3
118
0
3
Order By: Relevance
“…The search for the site and behavior of the pacemaker in the pregnant uterus has a long history (18,30,42). Several authors have suggested that the fundus of the uterus was the main origin of these contractions (2,3,8).…”
Section: Discussionmentioning
confidence: 99%
“…The search for the site and behavior of the pacemaker in the pregnant uterus has a long history (18,30,42). Several authors have suggested that the fundus of the uterus was the main origin of these contractions (2,3,8).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the abolition of the uterotonic effect of the extract by the dihydropyridine L-type calcium channel blocker, nifedipine, suggests a possible involvement of calcium mobilization in the activity of the extract. In the rat uterus, Ca 2þ entry to the cytosol occurs almost entirely through the L-type Ca 2þ channels (Wray et al, 2001), and extract of this plant has been shown to promote the entry of extracellular calcium into the cytosol through this type of channel (Uchendu & Nwankwo, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]. It is assumed that Ca 2ϩ entry following membrane depolarization occurs almost entirely via L-type VOCCs (31). This process is controlled by the membrane voltage and is stopped when membrane repolarization inactivates the channels.…”
Section: Description Of the Modelmentioning
confidence: 99%